Does political efficacy equally predict news engagement across countries? A multilevel analysis of the relationship among internal political efficacy, media environment and news engagement. (December 2020) - Lu, Shuning; Luqiu, Luwei Rose
This study serves as the first to examine the mechanism of news engagement with regard to the three proposed dimensions (i.e. overall news engagement, user-user news engagement, and user-content news engagement) across 36 countries. We employed hierarchical linear modeling to test how internal political efficacy and media environment—both political and technological, shape news engagement based on the multinational cross-sectional survey data ( N = 72, 930). The findings showed that internal political efficacy was positively associated with news engagement. Press freedom was negatively associated with user-content news engagement; Internet penetration was negatively associated with the three indicators of news engagement. Press freedom negatively moderated the effect of internal political efficacy on user-content news engagement. The study advances our understanding about the individual and contextual mechanisms of news engagement. It also renders significant implications for news organizations to consider the role of media environment while practicing engagement.